The role and capacities of large-scale actor coalitions in shaping sustainability transformations - Sofia Maniatakou; Per Olsson; Peter Søgaard Jørgensen (Global Sustainability)
Abstract Non-Technical Summary Several transnational corporations, investors, international organizations, and philanthropies have formed coalitions to respond to global social and environmental challenges. Do these coalitions, consisting of large-scale actors, have the capacity to contribute to the sustainability transformations that are needed, or do they perpetuate the same systemic dynamics that created the problems in the first place? We investigate this question by comparing publicly available information from five coalitions working on financial and food systems sustainability.